2023
DOI: 10.1007/s00203-023-03549-1
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly synthesized silver nanoparticles from endophytic fungus Phyllosticta owaniana: KUMBMDBT-32 and evaluation of biomedical properties

Abstract: The present study focused on biosynthesis of silver nanoparticles from an endophytic fungus isolated from the medicinal plant Abrus precatorius. The endophytic fungus was identi ed as Phyllosticta owaniana KUMBMDBT-32 (NCBI Accession number MW007919). The fungus was cultured in submerged fermentation and extracted with ethyl acetate (1:1 V/V). The extract was subjected to GC-MS analysis which have revealed the presence of 42 bioactive compounds of secondary metabolites. Synthesized silver nanoparticles were ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Green synthesis of AgNPs has also been explored extensively due to their antioxidant and anti-inflammatory activities [63,64]. In medicine, the interaction of nanoparticles with skin cells, including neonatal human epidermal keratinocytes, was studied to understand their impact and potential toxicity [65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green synthesis of AgNPs has also been explored extensively due to their antioxidant and anti-inflammatory activities [63,64]. In medicine, the interaction of nanoparticles with skin cells, including neonatal human epidermal keratinocytes, was studied to understand their impact and potential toxicity [65].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that these extracts induced significant effects in vitro on different cancer lines, from breast cancer, colorectal cancer, bladder cancer, and prostate cancer, to leukemia [77][78][79][80][81]. Even the green synthesized AgNps demonstrated effectiveness in inhibiting cancer cell growth [63,82] and in inducing apoptosis in leukemia cells [83], and that the size and shape of AgNPs play a crucial role in exerting their biological activities on cancer cells.…”
Section: Discussionmentioning
confidence: 99%